EVALUASI PROGRAM PENCEGAHAN KECELAKAAN KENDARAAN DI PT FREEPORT INDONESIA - Oong Supratikno; Rizal Syarief; Dikky Indrawan (School of Business, Bogor Agricultural University (SB-IPB), 2021)
PT Freeport Indonesia (PT FI) applies strict rule to prevent vehicle accident. In fact, the number of vehicle accident is recorded highly enough. The objectives of the research are to (1) identify the most influential factor to the number of light vehicle accident; (2) formulate the right planning to reduce the number of light vehicle accident; (3) provide recommendation to PT FI management to reduce the number of light vehicle accident at PT FI. The research applies used primary and secondary data resource. Secondary data taken from report data of vehicle accident is grouped using Contributory Factor Interaction Model (CFIM) to identify the causing factor of the accidents cause. Afterwards, identification of program improvement planning is conducted using Analytical Hierarchy Process (AHP). The result of the research conveys that the most influential factor of light vehicle accident at PT FI is unsafe behavior of the driver. The right planning to reduce the number of light vehicle accident at PT FI, it is suggested to is conduct the human resources planning by providing training to improve soft skill and hard skill of the driver. Based on this influential factor and the AHP result, the right planning as a recommendation to PT FI Management to reduce the number of light vehicle accident is by applying short- and long-term human resources planning. Keywords: vehicle accident, ahp, cfim, prevention, light vehicle operation